SELF-HELP INITIATIVE AS PLATFORMS FOR LEADERSHIP, LEADING AT THE LOCAL LEVEL: A CASE STUDY OF RURAL WOMEN’S GRASSROOTS LEADERSHIP IN INDIA - Modi, Prabha; Padhiyar, Krishna; Patel, Subhana; Mehta, Siddhi (ShodhKosh: Journal of Visual and Performing Arts, 2026)
In rural India, Self-Help Groups (SHGs) have become vital platforms for women's grassroots leadership, empowering them to address local challenges despite gender and socioeconomic barriers. This case study focuses on Self-help Initiatives as a platform for SHGs under the National Rural Livelihood Mission (NRLM) in Gujarat’s tribal areas, highlighting their role in transforming women from marginalized participants to community leaders. Through qualitative data from 15 SHGs and interviews with 120 women, the research identifies key mechanisms for leadership emergence, including collective savings, microfinance, skill-building programs, and federated structures that enhance women's voices in local governance. The study outlines three leadership archetypes—economic mobilizers, social advocates, and institutional navigators—who successfully improve household incomes by 35% and increase women’s participation in panchayats by 28%. Nonetheless, challenges like elite capture and digital divides remain. By applying a feminist leadership framework aligned with sustainable development goals (SDGs 5 and 8), the research emphasizes the potential of SHGs for gender-responsive governance and calls for policy reforms to support scalable models for rural empowerment.